Idealized single-forcing GCM simulations with GFDL CM2.1 ... - Erb, Michael; Broccoli, Anthony; Raney, Bryan (Zenodo, 2018)
This repository contains a set of single-forcing general circulation model (GCM) simulations run with the Geophysical Fluid Dynamics Laboratory (GFDL) Climate Model 2.1 (CM2.1). In each of these equilibrium simulations, one climate forcing was altered while all others were held constant at preindustrial levels, modeling the climate response to individual climate forcings. Simulations were run for obliquity (low and high obliquity), precession (four phases of the precession cycle with high eccentricity, and one simulation with eccentricity set to zero), half CO2, and LGM-sized ice sheets. The values chosen for the orbital simulations represent the extreme values of the past 900 thousand years. Simulations were run for at least 500 years, and forcings do not change from year to year. The uploaded files are 100 year annual-means and monthly climatologies. Variables are presented for the atmosphere, ocean, sea ice, and land. Monthly ocean files for most of the simulations are not currently available; please ...